Ascidae, Blattisociidae and Melicharidae (Acari: Mesostigmata): zoogeographic analyses based on newly available databases - Santos, Jandir C.; Rueda-Ramírez, Diana; Demite, Peterson R.; de Moraes, Gilberto J. (Zootaxa, 2018)
Until recently, species of the families Ascidae Voigts & Oudemans, Blattisociidae Garman and Melicharidae Hirschmann were considered to belong to a single family, Ascidae, based on their similarity in external morphology. Databases on the distribution and biology of species in those families have been collected are now freely available. This information allows the first zoogeographic analysis of these groups. Almost 2200 records obtained from about 820 publications were entered into the databases, which are periodically updated. The countries with the highest known diversity of mites of these groups are: Ascidae—Russia (56), United States of America (42), China (37) and Poland (36); Blattisociidae—China (47), United States of America (41), Ecuador (38), India (33) and Poland (32); Melicharidae—United States of America (46), Brazil (23), Ecuador (20) and Poland and Germany (15). No species of these families have been reported from about 44% of the countries, most probably because of inadequate sampling effort. Comparing the species composition of the different regions, Jaccard similarity indexes were low, being higher between the Palaearctic and Saharo-Arabian regions for the ascids (0.15), between the same regions for the blattisociids (0.19) and between the Neotropical and Panamanian regions for the melicharids (0.18). These data are compatible with the results of parsimony analyses of endemicity (PAE), in which those pairs of regions constituted distinct clades. The analyses suggest that Ascidae probably originated in the Palaearctic region, whereas Blattisociidae and Melicharidae probably originated somewhere in the Neotropical or Panamanian regions.